Novel Modifications in RNA - Phelps, Kelly (2011)
The last several years have seen numerous reports of new chemical modifications for use in RNA. In addition, in that time period, we have seen the discovery of several previously unknown naturally occurring modifications that impart novel properties on the parent RNAs. In this review, we describe recent discoveries in these areas with a focus on RNA modifications that introduce spectroscopic tags, reactive handles, or new recognition properties.